Expression of Ki67 as potential biomarker in oral submucous fibrosis: An immunohistochemical study - K A Kamala; Sujata R Kanetkar; Kailash D Datkhile; S Sankethguddad (Wolters Kluwer Medknow Publications, 2022)
Background: Oral submucous fibrosis (OSMF) is a potentially malignant disorder (PMD) known to transform into oral cancer. One of the important hallmarks of malignant transformation is the uncontrolled growth rate, commonly reflected as increased cell proliferation which can be significantly detected by proliferative markers such as a high Ki-67 index. Aim: The aim of this study is to evaluate the degree and pattern of expression of Ki67 in OSMF, oral squamous cell carcinoma (OSCC) and in normal mucosal (NOM) patients and to correlate the Ki67 expression with clinical and histological grading of OSMF and OSCC patient. Materials and Methods: A prospective cross-sectional study was conducted over a duration of two years. An immunohistochemical study was performed for Ki76 expression on 35 cases of OSMF, 10 cases of OSCC and 10 normal mucosal patients. Statistical Analysis: Data were analysed using SPSS version 21. Chi-squared test was used to analyse the differences between the intensity levels in OSMF, OSCC and NOM. Results: Expression of Ki67 was significantly higher in OSMF than that of NOM samples but less than that of OSCC samples. Expression of Ki67 increased with increasing grade of clinical and histological stages. Conclusion: The study demonstrated a high incidence of Ki67 overexpression in OSMF and OSCC and showed a correlation between clinical and histological grading of OSMF and OSCC. Identification of high-risk oral PMDs and intervention at premalignant stages could constitute one of the key steps in reducing the mortality, morbidity and cost of treatment associated with malignant transformation of these diseases.